Online Game towards the Students’ Vocabulary of Technology and Information Department at UNIMUDA Sorong - Wardani.H, Rizqi Claudia; Saputro, Isnaini Eddy; Rusli, Siti Zuhriyanti (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2020)
The objective of this research is to know whether there is any significant influence of using game online and improvement of the students’ vocabulary of Technology and Information Department at UNIMUDA Sorong. This research was quantitative research. The researcher used pre-experimental research design. The population was the student of technology and Information . The sample were first, third, and fifth semesters. The researcher ask the student to play the game with English instruction and search the new word that they don’t know before. Researcher used test (pre-test and post-test) as the instrument in collecting data. The test consisted 20 question which is divided into multiple choice, matching, gap in the filling and making sentences form. The researcher analyzed the data using SPSS 22.0 for Windows. The result of data analysis using SPSS 22.0, the researcher gave interpretation toward “t” score by comparing t-value or t-count with t-table. The researcher interpretation that t-value (-7.121) with the significant value is 0.000. The score of t-table is (1,729) with significant level of 0.05 with df 19. It is known that t-value is higher than t-table (-7.121> 1,729) and P value smaller than 0,05. Therefore, there is a significant influence of using game online to improve the students’ vocabulary of Technology and Information Department at UNIMUDA Sorong.